Workshop on IoT EDUTrainee Utilization to Enhance Competency of Vocational School Teachers in IoT Implementation - Pramudita, Resa; Somantri, Maman; Fauzan, Mochamad Rizal; Rizqulloh, Muhammad Adli (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity aimed to enhance the competency of vocational school teachers in the electro field across Bandung Raya by providing training on the utilization of IoT EduTrainer technology. The workshop followed the ADDIE model, covering both theoretical and practical aspects of IoT implementation, including case studies on smart greenhouse monitoring, RFID-based door locks, and automated watering systems. Participants engaged in hands-on activities, gaining practical experience in setting up IoT systems using Blynk and MQTT platforms. The evaluation of the workshop, conducted through Likert-scale-based questionnaires, revealed a high level of participant satisfaction in terms of content quality, material delivery, and the practical sessions. Although the workshop was successful in achieving its objectives, feedback suggested that allocating additional time for hands-on exercises would further enhance participant understanding and the application of IoT concepts. This training has equipped teachers with valuable skills for integrating IoT into their curricula and has supported the development of future-ready students capable of thriving in the Industry 4.0 era.